2016
DOI: 10.1002/ijc.30255
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to fine particulate matter air pollution and the risk of lung cancer among participants of the Canadian National Breast Screening Study

Abstract: Recently, air pollution has been classified as a carcinogen largely on the evidence of epidemiological studies of lung cancer. However, there have been few prospective studies that have evaluated associations between fine particulate matter (PM2.5 ) and cancer at lower concentrations. We conducted a prospective analysis of 89,234 women enrolled in the Canadian National Breast Screening Study between 1980 and 1985, and for whom residential measures of PM2.5 could be assigned. The cohort was linked to the Canadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 47 publications
0
49
2
Order By: Relevance
“…Summaries of the study characteristics, methods, and key findings of each of these studies are shown in table 1. The pollution levels were similar in five of the six included studies with mean concentrations of these five studies ranging from 9.5±3.4 μg m −3 to 13.1±3.7 μg m −3 ; [23][24][25][26][27] the sixth study, one of the European-based study populations, had much higher pollution exposures with a mean of 28.3±2.5 μg m −3 [28].…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Summaries of the study characteristics, methods, and key findings of each of these studies are shown in table 1. The pollution levels were similar in five of the six included studies with mean concentrations of these five studies ranging from 9.5±3.4 μg m −3 to 13.1±3.7 μg m −3 ; [23][24][25][26][27] the sixth study, one of the European-based study populations, had much higher pollution exposures with a mean of 28.3±2.5 μg m −3 [28].…”
Section: Methodsmentioning
confidence: 82%
“…Six studies met the inclusion criteria for the meta-analysis. Four of these were based in North American study populations [23][24][25][26] with two studies based in European study populations [27,28]. The European study by Beelen and colleagues (2008) [29] was excluded, because updated results on that cohort with extended follow up time was provided in the later published study by Hart and colleagues (2015) [28].…”
Section: Methodsmentioning
confidence: 99%
“…All models were stratified by region (living in Toronto or not) at baseline. We conducted subgroup analyses to investigate potential effect modification by age group (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), 55-64, 65-74 and 75-85 years), sex (for lung cancer only), income level and selected comorbidities. Because we lacked information on menopausal status (a known risk factor for breast cancer) and the average age of menopause in Canada is 51 years, we conducted an additional stratified analysis by using 51 years as a cutoff to investigate whether there are potential differences for pre/postmenopausal breast cancer risk in relation to air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…conducted in North America and Europe that typically contained a small number of cases (with lung cancer cases ranging from 250 to 2,309), 7-10,41-43 which showed the increases in incident lung cancer per 10 μg /m 3 increase in PM 2.5 exposure varying from 6% to 43%, but was higher than that from a study in Netherlands (HR: 0.81; 1,940 cases). 8 These differences might be due to inherent difference in the characteristics of study subjects (e.g., females, 41,42 males, 43 nonsmokers 10 and general populations [7][8][9] ), different study designs (i.e., case-control 7 and cohort design [8][9][10][40][41][42][43] ), possible differences in the assessment of outcomes and PM 2.5 (e.g., land use regression models 9 and spatiotemporal interpolation methods 7,10,42 ), and differences in the sources and compositions of PM 2.5 , or chance. Interestingly, we found a somewhat strong association between lung cancer and NO 2 exposure (HR = 1.05; 95% CI: 1.03-1.07 for every 14 ppb increase in NO 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The investigators concluded that in certain regions of China, PM 2.5 imposes significant health risks that are even greater than those so far attributed to CS, thus action plans for Air Pollution Prevention and Control should be enforced, at least in specific geographical areas (76). Recently, strong associations between small cell LC and adenocarcinoma (hazard ratios: 1.53 and 1.44, respectively) and exposure to high levels of PM 2.5 have also been reported in a cohort of women of the Canadian Cancer Registry (77). In other studies, however, the effects of air pollution as a risk factor of LC were significantly attenuated after adjusting for several factors such as CS and occupational exposure, even if the influence of urbanization persisted (1,78).…”
Section: Air Pollutionmentioning
confidence: 99%